Glacier data - surface mass balance from Rabots Glaciär - Tarfala Research Station (Stockholm University, 2021)
Tarfala Research Station (2021). Glacier data - surface mass balance from Rabots Glaciär, 1982–2020 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Kl06fLDs-YUzlbvq2GmVkTNg
Keywords: Tarfala Research Station; Glacier mass balance/ice sheet mass balance; Glaciers; Winter surface mass balance; Winter surface mass balance; Summer surface mass balance; Summer surface mass balance; Net surface mass balance; Net surface mass balance; Year; Year; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap